2022
DOI: 10.3389/fpls.2022.824439
|View full text |Cite
|
Sign up to set email alerts
|

Carrot (Daucus carota L.) Seed Germination Was Promoted by Hydro-Electro Hybrid Priming Through Regulating the Accumulation of Proteins Involved in Carbohydrate and Protein Metabolism

Abstract: Asynchronized and non-uniform seed germination is causing obstacles to the large-scale cultivation of carrot (Daucus carota L.). In the present study, the combination of high voltage electrostatic field treatment (EF) with hydropriming (HYD), namely hydro-electro hybrid priming (HEHP), significantly improved all germination indicators of carrot seeds, and the promoting effect was superior to that of the HYD treatment. A tandem mass tags (TMT)-based proteomic analysis identified 4,936 proteins from the seeds, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Namely, HVED-exposed mallow seeds had 156% (2 nd day) and 90% (5 th day) higher germination percentage than untreated whilst HVED treated carrot seeds increased germination percentage by 19.4% (3 rd day), 3.5% (4 th day), 9.5% (6 th day), and 8.2% (9 th day), respectively. The study related to the impact of hydro-electro hybrid priming (HEHP) on carrot seed germination reveals beneficial effect towards classical hydropriming method (Zhao et al, 2022). The major findings of this study showed that HEHP treatment had ability to regulate the activity of differentially abundant proteins (DAPs) which control seed storage reserve and respiration metabolism.…”
Section: Effect Of Hved Treatment On the Germinationmentioning
confidence: 91%
See 1 more Smart Citation
“…Namely, HVED-exposed mallow seeds had 156% (2 nd day) and 90% (5 th day) higher germination percentage than untreated whilst HVED treated carrot seeds increased germination percentage by 19.4% (3 rd day), 3.5% (4 th day), 9.5% (6 th day), and 8.2% (9 th day), respectively. The study related to the impact of hydro-electro hybrid priming (HEHP) on carrot seed germination reveals beneficial effect towards classical hydropriming method (Zhao et al, 2022). The major findings of this study showed that HEHP treatment had ability to regulate the activity of differentially abundant proteins (DAPs) which control seed storage reserve and respiration metabolism.…”
Section: Effect Of Hved Treatment On the Germinationmentioning
confidence: 91%
“…Carrot seeds germination has been reported to increase by hydro-electro hybrid priming. Proposed mechanism is given in (Zhao et al 2022). The aim of this study was to investigate the possibilities of HVED treatment application to small seeds in a need of scarification due to physical dormancy or showing insufficient or uneven germination.…”
Section: Introduction mentioning
confidence: 99%
“…The proteomic profiles of aged and melatonin-primed oat ( Avena sativa L.) seeds revealed that improved antioxidant capacity and restoration of membrane integrity were essential to promote germination performance ( Yan and Mao, 2021 ). The impact of hydro-electro hybrid priming applied to carrot ( Daucus carota L.) seeds was explored through proteomics, highlighting the concerted regulation of protein synthesis and degradation, and respiratory metabolism ( Zhao et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%